KEBERLAKUAN MODEL HB-GFT SISTEM n-HEKSANA – MEK – AIR PADA EKSTRAKSI CAIR-CAIR KOLOM ISIAN - Agus Mirwan (INFO-TEKNIK, 2010)
Liquid-liquid extraction in packed column is a process of liquid phase separation in which a liquid solution (the feed) is contacted with an immiscible or nearly immiscible liquid (solvent). This type of extraction is a kind of vertical column extraction type without agitator (unagitated column) besides spray column and plate column. Good operation of liquid-liquid extraction hardly influenced by solute transfer characteristic. This characteristic can be quantification with a value so-called with mass transfer coefficient. Mass transfer coefficient is importance in order to be known in scheme of liquid-liquid extraction column and the values can be searched by using estimation models of mass transfer coefficient either in dispersion phase and also continue phase.The aim of this research is to prove model applying Handloss-Baros - Garner-Foord-Tayeban (HB-GFT) at liquid-liquid extraction process using transparent column prototype and packing type of small sphere with various of flow rate continue phase and dispersion phase at circulation drop spread (Re = 10 - 200). From this research got that packing type, droplet size, and flow rate phase (dispersion and continue) gives influence that is enough significant to mass transfer process that expressed with overall mass transfer coefficient (KOD). Flow rate and composition each phase in inlet and outlet column data are analyzed by using gas chromatography equipment (GC) that showed more and more big dispersion phase (Qd) flow rate, mass transfer coefficient (KOD) more and more small. This caused that drop diameter measure along the length of packing column assumed to be same. And model applying HB-GFT for internal circulation drop dynamics (170<Re<200) is best combination in determination of KOD with deviation standard equal to 3,2%.